2020
DOI: 10.1108/pijpsm-06-2019-0095
|View full text |Cite
|
Sign up to set email alerts
|

The “power few” of missing persons’ cases

Abstract: PurposeThe purpose of this paper is to test the “power few” concept in relation to missing persons and the locations from which they are reported missing.Design/methodology/approachData on missing persons’ cases (n = 26,835) were extracted from the record management system of a municipal Canadian police service and used to create data sets of all of the reports associated with select repeat missing adults (n = 1943) and repeat missing youth (n = 6,576). From these sources, the five locations from which repeat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
2
17
1
Order By: Relevance
“…Investigators have also found that, specific to these places, other harm and adverse events with a high likelihood of occurring are alcohol consumption, overdose death, self-neglect, aggression, violence, sexual assault, and medication non-compliance (Bowers et al, 2003;Carr, 2006;Dickens and Campbell, 2001;Pages et al, 1998;Tammelleo, 1999). For missing person reports from other locations, however, harm befalls anywhere from zero around six per cent of cases (NCA, 2019;Huey, Ferguson, & Kowalski, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigators have also found that, specific to these places, other harm and adverse events with a high likelihood of occurring are alcohol consumption, overdose death, self-neglect, aggression, violence, sexual assault, and medication non-compliance (Bowers et al, 2003;Carr, 2006;Dickens and Campbell, 2001;Pages et al, 1998;Tammelleo, 1999). For missing person reports from other locations, however, harm befalls anywhere from zero around six per cent of cases (NCA, 2019;Huey, Ferguson, & Kowalski, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lorna Ferguson https://orcid.org/0000-0002-4077-9501 Notes 1. As an example of why these classifications can be important, a recent study by Huey et al (2020) found that "habitual/chronic" missing person cases ranged from three previous missing person reports to 144 prior reports. 2.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, calls for police service to locate persons from such places hold the potential to draw upon and drive a sizable proportion of policing resources (Hayden & Shalev CrimRxiv • How Far Do They Go? : A Spatial Examination of Missing Persons from Hospitals 3 Greene, 2018; Huey, Ferguson, & Kowalski, 2020). In the broader literature examining other occurrences similarly impacting policing (i.e., mental health-related service calls), recognizing the rise of austerity policing and dwindling police resources but increasing and expanding service demands has led police and researchers alike to investigate how police efficiency and effectiveness can be maximized when responding to significant service calls (Huey, Cyr, & Ricciardelli, 2016;Shore & Lavoie, 2019;Koziarski, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…, 2009; Parr and Stevenson, 2013; Hayden and Shalev-Greene, 2018; Ferguson and Huey, 2020; Ferguson, 2021). As a result, calls for police service to locate persons from such places hold the potential to draw upon and drive a sizable proportion of policing resources (Hayden and Shalev-Greene, 2018; Huey et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%